Cloning leishmania telomeres in yeast by complementation - Espinoza, José (2003)
Leishmania telemores were cloned in yeast by complementation using a half arm of the yeast artificial chromosome vector pJS97. A single copy marker associated to the telomere (YT2) located 6 kb away from one end of a megabase size chromosome of 1116c8 was cloned by end rescue and DNA sequenced. The sequence of 1479 bp did not show a significant homology with any sequence stored in GenBank. Leishmania telomeres are amenable to be cloned and maintained in yeast, this approach will facilitate the analysis of telomere and subtelomere regions which are usually underrepresented in genomic libraries.